ANALISIS KETERSEDIAAN INPUT UNTUK MENYELENGGARAKAN PONEK DI RUMAH SAKIT UMUM SWASTA DI KOTA DENPASAR - Dewi, Ni Wayan Purnama; Nopiyani, Ni Made Sri (ARCHIVE OF COMMUNITY HEALTH, 2020)
ABSTRACT Hospital with 24 hours Comprehensive Emergency Neonatal Obstetric Services (PONEK) is part of referral system for maternal and neonatal emergency services. This services plays pivotal role in reducing maternal and newborn mortality. Private hospitals in Denpasar have been received PONEK training since 2015, however there was no evaluation has been conducted regarding input availability during its implementation in private hospitals in Denpasar. Therefore, this study aims to find out the availability of PONEK inputs in private hospitals. This research is an evaluative study. Data collection was carried out by observation, study documentation, and in-depth interviews at Puri Raharja Hospital and Prima Medika Hospital. This study was using purposive sampling method. Observation was carried out in washing hand areas and processing equipment in maternal and neonatal units and stabilization areas in obstetric and neonatal rooms in the emergency room, delivery room, operating room, intensive care unit, area lactation and incubator washing area. In-depth interviews were conducted with 4 informants from the two hospitals consisting of 1 head of medical services and 1 chief of the PONEK team. Study found that the availability of human resources in private hospitals in the city of Denpasar is still lacking. Team is available according to the standards of the essential PONEK Team. Funds for the implementation of PONEK are available which are used to provide facilities, infrastructure and increase human resource capacity. The availability of facilities and infrastructure is also still lacking. There are 2 obstacles in the provision of facilities and infrastructure which are related to limited space and funds. Guidelines for implementing 24-hour PONEK in hospitals and Standard Operating Procedures related to maternal and neonatal emergency services are available in hospitals and have been socialized. There is Decree of the Hospital Director regarding the Formation of the PONEK Hospital Team as supporting policy. It can be concluded that the availability of inputs in the implementation of PONEK in Private Hospitals in Denpasar City has not been optimal. There is a need to improve HR, facilities and infrastructure as well as a review of operational process standards. Keywords: Input Availability, Organizing PONEK, Private Public Hospital